MyFC partners with Jotech/ECar for hybrid electric vehicle concept. Issue 3 (March 2020) - Unknown
Abstract : Swedish micro fuel cell company myFC is working with its strategic partner Jotech/ECar Sweden, to showcase a fully functional concept electric vehicle to stakeholders and the public in the summer.